2014
DOI: 10.1172/jci77598
|View full text |Cite
|
Sign up to set email alerts
|

Spastic paraplegia proteins spastizin and spatacsin mediate autophagic lysosome reformation

Abstract: Autophagy allows cells to adapt to changes in their environment by coordinating the degradation and recycling of cellular components and organelles to maintain homeostasis. Lysosomes are organelles critical for terminating autophagy via their fusion with mature autophagosomes to generate autolysosomes that degrade autophagic materials; therefore, maintenance of the lysosomal population is essential for autophagy-dependent cellular clearance. Here, we have demonstrated that the two most common autosomal recessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
245
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(261 citation statements)
references
References 42 publications
16
245
0
Order By: Relevance
“…Moreover, spastizin and spatacsin were essential for the initiation of lysosomal tabulation, and their loss resulted in depletion of free lysosomes, competent to fuse with autophagosomes, and a resultant accumulation of autolysosomes, reflecting a failure in autophagic lysosome reformation [58]. These results are consistent with recent findings in fibroblasts from SPG11 and SPG15 patients, of selective enlargement of LAMP1-positive structures, and endolysosomal abnormalities, and support a converging mechanism for the two disorders that links dysfunction of the autophagy/lysosomal biogenesis machinery to neurodegeneration [59,60]. …”
Section: Discussionsupporting
confidence: 78%
“…Moreover, spastizin and spatacsin were essential for the initiation of lysosomal tabulation, and their loss resulted in depletion of free lysosomes, competent to fuse with autophagosomes, and a resultant accumulation of autolysosomes, reflecting a failure in autophagic lysosome reformation [58]. These results are consistent with recent findings in fibroblasts from SPG11 and SPG15 patients, of selective enlargement of LAMP1-positive structures, and endolysosomal abnormalities, and support a converging mechanism for the two disorders that links dysfunction of the autophagy/lysosomal biogenesis machinery to neurodegeneration [59,60]. …”
Section: Discussionsupporting
confidence: 78%
“…Some exemplary clusters of shared or interacting pathways underlying ASS diseases are: Phospholipid metabolism , including the genes PNPLA6 , 12,40,41 PLA2G6, DDHD1 (SPG 28), DDHD2 (SPG54 42 ), CYP2U1 (SPG49), and ABHD12 43 (for further overview, see references 40 and 44 ). Sphingolipid metabolism , including the genes FA2H , 15 GBA2 , 33,45 GALC, HEXA, ASA, PSAP , and GLB1 . Autophagy-lysosomal activity , including the genes SPG15 , SPG11 , 46,47 ATP13A2 (SPG78), 48,49 NPC1 , and NPC2 disease. 50-55 …”
Section: Common Pathophysiological Pathways and Mechanisms In Ataxiasmentioning
confidence: 99%
“…Autophagy-lysosomal activity , including the genes SPG15 , SPG11 , 46,47 ATP13A2 (SPG78), 48,49 NPC1 , and NPC2 disease. 50-55 …”
Section: Common Pathophysiological Pathways and Mechanisms In Ataxiasmentioning
confidence: 99%
“…It was suggested that axonal defects were observed in patients with nonsense and splice variants in SPG11 , which is further supported by a functional study using a mouse model (PĂ©rez-BrangulĂ­ et al 2014). Loss of Spatacsin also causes accumulation of autolysosomes and deprivation of free lysosomes, thereby disrupting the autophagic lysosome reformation pathway, ultimately leading to neurodegeneration (Chang et al 2014). In this study, we have identified compound heterozygous variants in SPG11 that were predicted to cause truncation of the corresponding protein.…”
Section: Resultsmentioning
confidence: 99%
“…Onset time is childhood to early adult (Shibasaki et al 2000; Casali et al 2004; Winner et al 2004; Olmez et al 2006; Hehr et al 2007). A majority of SPG11 cases are caused by homozygous recessive or compound heterozygous variants in the SPG11 gene (Stevanin et al 2007, 2008), which codes for the Spatacsin protein with a role in axonal maintenance, cargo trafficking (PĂ©rez-BrangulĂ­ et al 2014), and autophagy (Chang et al 2014). Because of overlapping phenotypes in different hereditary spastic paraplegia (HSP) subtypes (Pensato et al 2014), diagnosis of SPG11 is often supplemented with evidence from molecular genetics testing.…”
Section: Case Presentationmentioning
confidence: 99%